Red, white, and processed meat consumption related to inflammatory and metabolic biomarkers among overweight and obese women - Shiraseb, Farideh; Hosseininasab, Dorsa; Mirzababaei, Atieh; Bagheri, Reza; Wong, Alexei; Suzuki, Katsuhiko; Mirzaei, Khadijeh (Frontiers in Nutrition, 2022)
Background: Considering that a high meat intake is directly associated with obesity, it is critical to address the relationship between consuming different types of meat with inflammation and metabolism in overweight and obese cohorts. Thus, we evaluated the association between red, white, and processed meat consumption with inflammatory and metabolic biomarkers in overweight and obese women. Methods: The current cross-sectional study was conducted on 391 overweight and obese Iranian women. Dietary intake was obtained from a food frequency questionnaire (FFQ) with 147 items. The anthropometric measurements, serum lipid profile, and inflammatory markers were measured by standard protocols. All associations were assessed utilizing one-way analysis of variance (ANOVA), analysis of covariance (ANCOVA), and linear regression models. Results: In the adjusted model, it was established that higher intake of processed meat had a significant positive association with leptin levels (β: 0.900, 95% CI: 0.031;1.233, p=0.015). Moreover, after considering the confounders, a significant positive association between processed meat and macrophage inflammatory protein (MCP-1) levels was observed (β: 0.304, 95% CI:0.100;1.596, p=0.025). Positive significant associations between high-sensitivity C-reactive protein (hs-CRP) (β:0.020, 95% CI:0.000;0.050, P=0.014) and plasminogen activator inhibitor 1 (PAI-1) (β:0.263, 95% CI:0.112;0.345, p=0.053) and MCP-1 (β:0.490, 95% CI: 0.175;1.464, p=0.071) levels with red meat were also shown; while there was a significant negative association between red meat and the homeostasis model assessment of insulin resistance (HOMA-IR) (β:-0.016, 95% CI: -0.022, -0.001, p=0.033). Furthermore, a significant negative association were established following confounding adjustment between Galectin-3 (Gal-3) (β: -0.110, 95% CI:-0.271;0.000, p=0.044), MCP-1 (β:-1.933, 95% CI:-3.721;0.192, p=0.022) and Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) (β:-0.011, 95% CI: -0.020,0.000, p=0.070) levels with high adherence of white meat intake. In contrast, a significant marginally positive association between PAI-1 levels and high adherence to white meat intake (β:-0.340, 95% CI:-0.751;0.050, p=0.070) has been shown. Conclusions: Higher red and processed meat consumption were positively associated with inflammatory and metabolic markers in overweight and obese women. In contrast, negative relationships between high adherence to white meat and various inflammatory and metabolic parameters were established. Further studies are needed to confirm the causality of these associations and potential mediating pathways.